2021
DOI: 10.1111/mec.15913
|View full text |Cite
|
Sign up to set email alerts
|

Ring distribution patterns—diversification or speciation? Comparative phylogeography of two small mammals in the mountains surrounding the Sichuan Basin

Abstract: The process of speciation has long fascinated evolutionary biologists, and one of the crucial steps in this process is population differentiation, which is the core of microevolutionary research (Foster et al., 1998;Rice & Hostert, 1993). Ring species are recognized as representing one illustration of speciation in nature, in which a chain of intergrading populations encircles a barrier and terminal forms coexist without interbreeding, providing a situation in which variation in space can be used to infer vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 113 publications
(206 reference statements)
0
5
0
Order By: Relevance
“…Genomic introgression likely contributes to the high genetic and morphological diversity of species endemic to Hengduan Mountains region, which acted not only as “cradle” and “museum” for species diversity but also as a “hybridisation zone” facilitating the admixture of genetically distinct populations during historical climatic and geological events (Macholán, 2013; Wang et al, 2021). These hybridisation zones are “natural laboratories” for biologists to study the formation and maintenance of species differences (Buggs, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic introgression likely contributes to the high genetic and morphological diversity of species endemic to Hengduan Mountains region, which acted not only as “cradle” and “museum” for species diversity but also as a “hybridisation zone” facilitating the admixture of genetically distinct populations during historical climatic and geological events (Macholán, 2013; Wang et al, 2021). These hybridisation zones are “natural laboratories” for biologists to study the formation and maintenance of species differences (Buggs, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…for species diversity but also as a "hybridisation zone" facilitating the admixture of genetically distinct populations during historical climatic and geological events (Macholán, 2013;Wang et al, 2021). These hybridisation zones are "natural laboratories" for biologists to study the formation and maintenance of species differences (Buggs, 2007).…”
Section: "Extended Ghost Introgression" In the Evolutionary History O...mentioning
confidence: 99%
“…The process of population isolation and differentiation, the core of micro-evolution, is one of the crucial steps for deciphering speciation, which has long fascinated evolutionary biologists ( Rice and Hostert, 1993 ; Wang et al, 2021 ). The Earth’s complex topographical history often generates opportunities for population isolation and differentiation ( Yan et al, 2010 ; Hou et al, 2014 ; Wang et al, 2021 ), especially for montane species. Mountain-building is often associated with tectonic forces, promoting population divergence through vicariance ( Hoorn et al, 2010 ; Smith et al, 2014 ; Simões et al, 2016 ; Schramm et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the Sichuan Basin and the surrounding forests functioned as refugia during glacial periods in China (Song et al, 2018 ). These areas are distributed in the eastern Himalayas and have long been considered a global biodiversity hotspot harboring many organisms (Wang et al, 2021 ). It could be inferred that during the LGM period, the mainland populations of Sclomina , except S. guangxiensis , were possibly distributed around the refugia and survived extinction until the glacial period ended.…”
Section: Discussionmentioning
confidence: 99%